Delaying Ripening of Cantaloupe fruits by Various Treatments During Storage - MAHMOUD A. SALEH; SAFAA ZAKARIA; AHMED S.A. SHEHATA (Future of Food: Journal on Food, Agriculture and Society, 2023)
This study was conducted for two seasons 2021 and 2022 to investigate the influence of Pu- trescine (PUT) at 0.1 or 0.2%, Spermine (SPM) at 0.1 or 0.2% and Chitosan (CS) at 1000 or 2000 ppm and in addition untreated control on quality attributes and delaying ripening of cantaloupe fruits (cv. Primal) during storage at 5º C for 28 days. The results indicated that all treatments were effective in reducing weight loss and colour changes and maintained, fruit firmness, TSS, sugar content, total carotenoids and overall appearance of fruits and modified atmosphere (CO2 %, O2 % and ethylene ppm) inside the package as compared with untreated control.The cantaloupe fruits treated with PUT at 0.1 %, SPM at 0.1 % and Chitosan at 1000 ppm were the most effective treatments in maintaining quality and delaying ripening during all storage periods. However, samples treated with SPM at 0.1 % showed the best quality avoid- ed the ripening, retarded the ethylene production and did not exhibit any changes in gen- eral appearance till the end of the storage period (28 days of storage at 5º C), while PUT at 0.2%, SPM at 0.2 % and chitosan at 2000 ppm rated good appearance at 21 days of storage